2012
DOI: 10.2337/dc12-0798
|View full text |Cite
|
Sign up to set email alerts
|

β- and α-Cell Dysfunctions in Africans With Ketosis-Prone Atypical Diabetes During Near-Normoglycemic Remission

Abstract: OBJECTIVEKetosis-prone atypical diabetes (KPD) is a subtype of diabetes in which the pathophysiology is yet to be unraveled. The aim of this study was to characterize β- and α-cell functions in Africans with KPD during remission.RESEARCH DESIGN AND METHODSWe characterized β- and α-cell functions in Africans with KPD during remission. The cohort comprised 15 sub-Saharan Africans who had been insulin-free for a median of 6 months. Patients in remission were in good glycemic control (near-normoglycemic) and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
1
29
2
1
Order By: Relevance
“…Furthermore, no statistical correlation was recorded in the present study between microalbuminuria and systolic/diastolic blood pressure. This is contrary to the findings of Ghosh et al [13]. Similar results have been reported by studies [16].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, no statistical correlation was recorded in the present study between microalbuminuria and systolic/diastolic blood pressure. This is contrary to the findings of Ghosh et al [13]. Similar results have been reported by studies [16].…”
Section: Discussioncontrasting
confidence: 71%
“…Varied results have also been reported in diabetics in sub-Saharan Africa. Choukem et al reported a prevalence of 31% [13] [16]. This variation can be attributed to factors such as differences in the populations (difference in ethnicity), definitions of MA, method of urine collection/storage, methods of measurement of MA, and sample size [12,17].…”
Section: Discussionmentioning
confidence: 99%
“…Such biomarkers of beta cell function and antibody status in this patient group are in agreement with its described heterogeneity. There was no case of diabetic ketoacidosis as none of our patients showed the clinical pattern that characterizes ketosis prone diabetes from patients in the same unit [30,31]. Further steps towards improved diagnosis in this heterogeneous patient group may require both C-peptide and GADA determinations, while additional markers could be developed following the recently described alterations in amino acid metabolism [32], in combination with determination of PAX4 risk haplotypes [33].…”
Section: Discussionmentioning
confidence: 99%
“…The group distribution was A + β − , A − β + , A − β − , and A + β + [22, 23]. Choukem et al showed that β - and α -cell dysfunctions both contribute to the pathophysiology of KPD; in addition, KPD displays a defect in β -cell sensitivity to glucose and has reduced β -cell mass [24]. Umpierrez et al demonstrated that hyperglycemia, but not lipotoxicity, played the crucial role in the pathogenesis of KPD in obese African patients [25].…”
Section: Discussionmentioning
confidence: 99%